The Reconstruction of Local Wisdom as Socio-Political Ethics: A Conceptual Inquiry into the Philosophy of Maja Labo Dahu in Bima Society - Zuriatin, Zuriatin; Nurhasanah, Nurhasanah; Junaidin, Junaidin; Nurlaila, Nurlaila (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to deeply investigate the philosophical and performative position of local values, particularly Maja Labo Dahu, within the socio-political ethical configuration of Bima society as a response to moral disorientation in the modern social order. Employing a historical-interpretive qualitative approach, this research integrates historical methods (heuristics, source criticism, interpretation, and historiography) with Pierre Bourdieu’s theory of social practice and cultural hermeneutics to uncover how the values of maja (shame) and dahu (fear) are constructed, reproduced, and interpreted transgenerationally as symbolic capital and public ethics. The findings reveal that Maja Labo Dahu is not merely a cultural relic, but a transcendental value system embodied in the habitus of Bima society, functioning as an imperative ethical institution that guides social actions and political legitimacy through affective and spiritual dimensions. This value system serves as a moral mechanism capable of disciplining social spaces without relying on the hegemony of formal regulation, thereby making it highly relevant as an ethical architecture for public policy, character education, and values-based leadership praxis. The study further indicates that the revitalization of local values such as Maja Labo Dahu can serve as a form of resistance against the erosion of public morality in the age of globalization, while simultaneously offering a conceptual foundation for constructing a substantive civic ethics rooted in the ontological relationship between humans, community, and the Divine within the Islamic-Bima cultural sphere.